Conglomerate Power without Market Power: The Effects of Conglomeration on a Risk-Averse Quantity-Adjusting Firm - Bradburd, Ralph M. (American Economic Review, 1980)
One of the interesting theoretical questions relating to conglomerate firms is whether conglomeration alone, unaccompanied by market power, can have any impact on firm behavior and market performance. Many of those who argue that conglomeration without market power is behaviorally neutral obtain their results by assuming, implicitly or explicitly, that the firm maximizes profits (see Jesse Markham; Richard Miller). Their arguments are quite straightforward: the absence of market power precludes profit-maximizing behavior based on predatory pricing, mutual forbearance, advertising advantages, etc.; and if one assumes a pure conglomerate, among whose subsidiaries' products there are no substitution or complementarity relations,' then the necessary condition for maximizing overall conglomerate profits is to maximize each subsidiary's profits by setting its output to the level at which marginal cost equals price -exactly what each subsidiary would have done if it were an independent purely competitive profit-maximizing firm. Thus, if one assumes that the firm maximizes total profits, conglomeration per se will be behaviorally neutral in the absence of monopoly power. Although the above argument is correct within the restrictions of its assumptions, our basic question is still not satisfactorily answered. Pure profit maximization is a very restrictive assumption, effectively implying-among other things-that the firm either operates in an environment in which there is no uncertainty, or that its management is indifferent to risk.2 Such an assumption seems especially restrictive and inappropriate for modeling the behavior of conglomerate firms, since these firms have claimed risk reduction to be a major goal of their merger activity (see Harold Geneen). The model developed below compares the optimal output of a risk-averse single product firm subject to demand uncertainty to that of a pure conglomerate subsidiary operating in the same market, assuming that the single product firm and conglomerate subsidiary are identically situated within that market3 (which I shall call the ith product market) and that their managements are equally risk averse. The results indicate that, except in very special circumstances, conglomeration will not be behaviorally neutral even if all subsidiaries possess no monopoly power at all.